Long-term outcomes of combined coronary bypass surgery and carotid endarterectomy in patients with type 2 diabetes - Yu. V. Belov; A. S. Ustinova; G. Kh. Yu; V. N. Kravchuk; R. A. Vinogradov; A. V. Korotkikh; D. V. Shmatov; V. Yu. Gavrilov; Y. A. Krasheninnikova; D. Yu. Morozov; A. B. Zakeryaev; P. V. Sukhoruchkin; et al. (Российский кардиологический журнал)
At present, there are no studies on the analysis of the incidence of complications in patients with concomitant lesions of the coronary and internal carotid arteries (ICA) after combined operation of carotid endarterectomy (CE) and coronary artery bypass grafting (CABG) against the background of type 2 diabetes (T2D). However, there is no doubt that this condition can be a predictor of cardiovascular and wound complications during in-hospital and long-term postoperative periods.Aim. To study in-hospital and long-term outcomes of combined CABG+CE in patients with and without type 2 diabetes.Material and methods. This multicenter retrospective study for the period from January 2015 to December 2019 included 653 patients with concomitant atherosclerotic lesions of ICA and coronary arteries, who underwent combined CE+CABG. Depending on presence of type 2 diabetes, 2 groups were formed: group 1 (n=183) — patients with type 2 diabetes; group 2 (n=471) — patients without type 2 diabetes. The duration of postoperative follow-up was 37,8±14,9 months.Results. During hospitalization, significant differences in the incidence of death (group 1 =1,1%; group 2 =1,0%; p=0,97), myocardial infarction (MI) (group 1 =1,1%; group 2 =0,8%; p=0,76), bleeding events (group 1 =1,1%; group 2 =0,8%; p=0,76) were not detected. However, stroke (group 1 =3,8%; group 2 =0,4%; p=0,0008), sternal wound infection and mediastinitis (group 1 =3,3%; group 2 =0,2%; p=0,0006) were significantly more often developed in patients with type 2 diabetes.In the long-term follow-up period, death (group 1 =6,6%; group 2 =1,1%; p<0,0001), MI (group 1 =4,9%; group 2 =0,8%; p=0,0008), stroke (group 1 =7,7%; group 2 =1,5%; p<0,0001), ICA restenosis (group 1 =8,8%; group 2 =1,6%; p<0,0001), repeated emergency myocardial revascularization (group 1 =7,2%; group 2 =1,5%; p=0,0002), repeated emergency cerebral revascularization (group 1 =8,8%; group 2 =1,6%; p<0,0001) were significantly more often recorded in patients with type 2 diabetes.Kaplan-Meier curve analysis and its comparison using the log rank test revealed that the death, MI, and stroke were also significantly more often observed in patients with type 2 diabetes (p=0,0007, p=0,003, p<0,0001, respectively).Conclusion. Patients with type 2 diabetes who are referred for combined CE+CABG are at an increased risk of stroke, sternal wound infection and mediastinitis in the in-hospital postoperative period, as well as all adverse cardiovascular events in the long-term follow-up period.